Aeromagnetic and gravity imaging of the Rennick pull-apart basin in East Antarctica - fausto Ferraccioli; Egidio Armadillo; Laura Crispini; Andreas Laufer; Alessandro Ghirotto; Antonia Ruppel (2020)
The extent and impact of Cenozoic extension and transtension within the Transantarctic Mountains sector of East Antarctica remains both poorly understood and controversial. Here we present results from the REGGAE project that combines an analyses of aeromagnetic, aerogravity and land-gravity and bedrock topography data to help constrain the extent, architecture and kinematics of the largest Cenozoic pull-apart basin recognised so far in East Antarctica, the Rennick Graben (RG). Enhanced potential field images reveal the extent of part of a Jurassic tholeiitic Large Igneous Province preserved within the RG, and define the inherited structural architecture of the Ross-age basement in northern Victoria Land. Highly magnetic arc basement is imaged beneath the northern segment of the RG, while a subglacial thrust fault belt is unveiled between the western flank of the RG and the eastern margin of Wilkes Subglacial Basin (WSB). We interpret the RG as a major composite right-lateral pull-part basin that extends from the Oates Coast to the Southern Cross Mountains crustal block and further propose that it is kinematically connected with both the western edge of the West Antarctic Rift System and the eastern margin of the WSB. Our findings suggest that the RG is part of a wider distributed region of the continental lithosphere in East Antarctica that was deformed in response to Cenozoic transtensional stresses, which may also have facilitated propagation of transform faulting in the adjacent oceanic lithosphere located between southeastern Australia and Tasmania.